Dampak Kondisi Makroekonomi terhadap Deposito Perbankan Syariah di Indonesia - Zaki Abdullah; Iman Sugema; Asep Nurhalim (AL-MUZARA'AH, 2018)
Changes in macroeconomic conditions have an impact towards financial industry, particularly in the banking industry. This research aims to look at the impact of global financial crisis and macreconomic variables towards the total deposits of Islamic banking in Indonesia with the VECM method. The period of this study using monthly data from January 2006 until December 2016. The results showed that the global financial crisis has no effect towards the total deposits of Islamic banking in Indonesia. Then, based on the analysis of Impulse Response Function (IRF), the response of total deposits of Islamic banking in Indonesia towards inflation, equivalent rate and lending rate is positive. While the shocks level of conventional banking interest rate and industrial growth is negatively responded by total deposits in Islamic banking. The Forecast Error Variance Decomposition (FEVD) analysis results showed that equivalent rate and interest rate offered by each banking system give most contributed among other variables.